The effect of using single-use plastics causes climate change in Indonesia - Panjaitan, Elsadday (Environmental, Social, Governance and Sustainable Business, 2024)
Background: The global environmental hazards that threaten people and nature are becoming increasingly clear. One of these hazards includes climate change that affects sea level rise, ocean warming, increased temperature and rainfall and tropical storms. Indonesia is one of the countries that has abundant natural resources with a high level of environmental damage. Indonesia as a tropical country is also one of the countries vulnerable to the negative impacts of climate change. With descriptive analysis method, this research aims to analyze Indonesia's position and strategy in Climate Change. The results show that, Indonesia in preparing action plans and funding uses a multi-sector coordination scheme implemented through the National Action Plan in Facing Climate Change and National Development Planning Response to Climate Change documents. The active role of the business community, academics, civil society organizations, development partners, and all elements of society is needed so that efforts to address climate change can be realized effectively to increase national resilience. The purpose of this study is to analyze public awareness of how dangerous it is to use single- use plastics and as an effort to reduce plastic waste in Indonesia. Methods: The method used in this research is quantitative with a survey approach. And the second research tries to explain the description of a particular object from one variable consisting of independent variables, namely campaign messages. The type of research used in this research is quantitative descriptive research. Findings: After analyzing the results of this study, we all know how important it is for us to protect the environment and control us to stop overusing materials that contain plastic because it is very damaging to the environment and causes a lot of climate change in Indonesia. Conclusion: As we know, Indonesia is the largest contributor to waste, especially the plastic waste that we always use in everyday life. I hope that the journal can broaden our horizons to always maintain our environment to be a good environment for survival.